KOMUNITAS BAKTERI RHIZOSFER TEH MELALUI APLIKASI BIOIMUNIZER (Chryseobacterium sp. dan Alcaligenes sp.) DENGAN METODE TERMINAL RESTRICTION FRAGMENT LENGTH POLYMORPHISM (T-RFLP) - Elin Savitri Aviani; Dwi Ningsih Susilowati; Siti Nur Jannah; Hermin Pancasakti Kusumaningrum (Jurnal Akademika Biologi, 2016)
Types of bacteria from the rhizosphere communities actually have been developed as bioimunizer but their consistency is still need further experiment about indigenous bacteria associated with rhizosphere of plants. This study aims to identification on the tea plant rhizosphere bacterial communities which in previous studies has been infected with E. vexans Massee and given bioimunizer as well as the checking existence Chryseobacterium sp. and Alcaligenes sp. The result research showed that communities of bacteria on control samples obtained through culturing Bacillus sp. (51.91%), Acidobacteria bacterium (39.42%) and Actinobacteria sp. (8.66%). Control sample through metagenom obtained Gemmatimonas aurantiaca (5.80%), Bacillus sp. (42.55%), Acidobacteria bacterium (23.45%) and Actinobacteria sp. (28.20%). Communities of bacteria in the samples treated by culturing obtained Gemmatimonas aurantiaca (3.58%), Bacillus sp. (30.76%), Pseudomonas sp. (5.55%) Acidobacteria bacterium (13.94%) and Actinobacteria sp. (46.16%). Communities of bacteria in the samples treated by metagenom found Bacillus sp. (10.66%), Acidobacteria bacterium (4.22%), Actinobacteria sp. (5.48%), Uncultured bacterium (1.49%), Alcaligenes sp. (36.95%) and Chryseobacterium sp. (46.82%). The existence of Alcaligenes sp. and Chryseobacterium sp. show consistency bioimunizer composition is applied. Communities of bacteria on metagenom have diversity and evenness level higher than the culturing approach. Keywords: bacterial communities, T-RFLP, Chryseobacterium sp., Alcaligenes sp.